2014
DOI: 10.1002/ece3.1158
|View full text |Cite
|
Sign up to set email alerts
|

Survival relative to new and ancestral host plants, phytoplasma infection, and genetic constitution in host races of a polyphagous insect disease vector

Abstract: Dissemination of vectorborne diseases depends strongly on the vector's host range and the pathogen's reservoir range. Because vectors interact with pathogens, the direction and strength of a vector's host shift is vital for understanding epidemiology and is embedded in the framework of ecological specialization. This study investigates survival in host-race evolution of a polyphagous insect disease vector, Hyalesthes obsoletus, whether survival is related to the direction of the host shift (from field bindweed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 53 publications
(109 reference statements)
2
14
0
Order By: Relevance
“…Faster growth on phytoplasma-infected plants could provide a fitness advantage as the insects are then not exposed as long to predators and entomopathogens. Previous studies on phytoplasma infection have reported positive (Sugio et al, 2011a;Maixner et al, 2014), negative (Mayer et al, 2011), and neutral effects (Vega et al, 1995) on the performance of insect vectors. There are, however, fewer data on the impact of plant bacterial infections on nonvector species.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Faster growth on phytoplasma-infected plants could provide a fitness advantage as the insects are then not exposed as long to predators and entomopathogens. Previous studies on phytoplasma infection have reported positive (Sugio et al, 2011a;Maixner et al, 2014), negative (Mayer et al, 2011), and neutral effects (Vega et al, 1995) on the performance of insect vectors. There are, however, fewer data on the impact of plant bacterial infections on nonvector species.…”
Section: Discussionmentioning
confidence: 95%
“…Phytoplasma infection has also been shown to increase levels of plant secondary metabolites, including phenolic compounds and hydrogen peroxide (Junqueira et al, 2004;Musetti et al, 2004;Musetti, 2009). Previous work has shown that these changes in the phytochemistry of phytoplasma-infected plants can influence the behavior of insect vectors (e.g., leafhoppers and psyllids) (Weintraub and Beanland, 2006;Mayer et al, 2008aMayer et al, ,b, 2011Kaul et al, 2009;Maixner et al, 2014). For example, Beanland et al (2000) showed that aster leafhoppers, Macrosteles quadrilineatus Forbes, live longer and have higher fecundity on asters [Callistephus chinensis (L.) Nees] infected by the aster yellows phytoplasma than on uninfected plants.…”
Section: Introductionmentioning
confidence: 99%
“…H . obsoletus populations affiliated with these plants are well studied in central Europe [ 14 , 25 , 28 ], especially along the northernmost border of the species distribution range [ 7 , 15 , 29 ]. Recent research has also confirmed these associations and its epidemiological importance in southeastern Europe [ 13 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, epidemiology of a pathogen like ‘ Ca . Phytoplasma aurantifolia’ is intimately associated with the evolution of the insect–plant interactions [27,52]. When generalist pathogens are spread by polyphagous vectors, the number and diversity of interactions between pathogen, host and alternative hosts are increased [49].…”
Section: Resultsmentioning
confidence: 99%